The ATLAS IBL BOC prototype - Schroer, Nicolai (Journal of Instrumentation, 2011)
The Pixel Detector of the ATLAS experiment at CERN will be upgraded with an Insertable B-Layer (IBL) in 2013. To handle the data readout the currently used VME card pairs consisting of a back of crate card (BOC) and a read out driver (ROD) are being redesigned. This paper presents details of the hardware design of the new BOC prototype, which takes advantage from modern FPGA technology and commercial optical modules and abandons the need for a variety of custom components used on the old card. Also the throughput is four times higher and additional features are implemented.
Topical Workshop on Electronics for Particle Physics 2011, 26-30 September 2011, Vienna, Austria
Gesehen am 26.10.2022